Prevention of Bullying of Students in Educational Institutions and the Application of Legal Sanctions - Saifullah, Saifullah (Technium Social Sciences Journal, 2022)
This is a qualitative research with a case study approach. This research is intended to answer the questions how the sanctions are applied by schools for bullying children and how the law enforcement for bullies is applied. Data was collected by means of semi-structured interviews with 5 informants consisting of a psychologist, a legal practitioner and 3 parents whose children were victims of bullying. Cases of bullying that occur in schools receive less attention from teachers, academic staff and school principals. In general, bullying is still considered an ordinary child delinquency and behaviour, even though the impact of bullying is very dangerous for students who become victims. For this reason, every teacher, staff, principal must have sufficient knowledge regarding bullying issues in order to create an activity program that aims to prevent bullying and every parent must also pay attention to their children and understand that currently there is a law related to the problem of bullying and it is hoped that parents will have the courage to report to the authorities in order to provide a deterrent effect not only to the bullies but also to those who cover up the case.